Jakarta Non-Chinese Ancestry Indonesian Students’motivation of Chinese Studying - Fu Ruo Mei; Huang Yan- Ling; Ye Mei- Yean (Humaniora, 2011)
More and more non-Chinese ancestry Indonesian begin to learn Chinese,some of them even choose Chinese as their major in University.The survey of four major Chinese departments in Jakarta shows that intrinsic motivation is the most important motivation of Chinese studying. Interests and passion to Chinese language and culture encouraged the non-Chinese ancestry Indonesian students to study Chinese. To assist them overcome their difficulties in studying is very important for Chinese education in Indonesia.